2022
DOI: 10.1093/ofid/ofac027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Virological Contributions to COVID-19 Outcomes in a Longitudinal Cohort of Hospitalized Adults

Abstract: While several demographic and clinical correlates of Coronavirus Disease 2019 (COVID-19) outcome have been identified, their relationship to virological and immunological parameters remain poorly defined. To address this, we performed longitudinal collection of nasopharyngeal swabs and blood samples from a cohort of 58 hospitalized adults with COVID-19. Samples were assessed for SARS-CoV-2 viral load, viral genotype, viral diversity, and antibody titer. Demographic and clinical information, including patient b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
5
13
0
Order By: Relevance
“…We report that no single mutation was identified to be specific to, or associated with, severe disease. Our report supports previous findings that known factors such as age over 60, immunosuppression, and other co-morbidities previously identified including diabetes and high body mass have been reported to be more significantly associated with disease severity than any specific SARS-CoV-2 VOC [ 34 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We report that no single mutation was identified to be specific to, or associated with, severe disease. Our report supports previous findings that known factors such as age over 60, immunosuppression, and other co-morbidities previously identified including diabetes and high body mass have been reported to be more significantly associated with disease severity than any specific SARS-CoV-2 VOC [ 34 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Resultssupporting
confidence: 92%
“…We report low cycle threshold (Ct) values for these patients, suggesting high levels of virus replication ( Supplemental Table S1 ). We also found agreement with other findings that older age, (e.g., >60) was a statistically significant factor correlated with severe disease outcomes [ 34 , 49 , 51 , 52 , 55 ]. We identified both Delta and Omicron lineages in hospitalized patients ( Figure 2 A).…”
Section: Discussionsupporting
confidence: 92%
“…The progression of ARDS during severe COVID-19 disease, as well as other severe respiratory viral infections, continues despite patients already having cleared the viral infection in the majority of cases, especially in immunocompetent hosts ( 44 ). It is during this period when the host is transitioning either to recovery or persistent inflammation that the outcome of infection is determined.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, similar observations had been hinted at in smaller studies comparing cancer patients with healthcare workers, comparing mildly and severely ill patients, and examining minor variants in samples from patients of different ages 2729 . Studies in which patients were longitudinally sampled have shown fluctuating numbers of minor variants over time, with little directional trend 9,30 . Combined with our data, this suggests that within-host diversity is temporally dynamic, but in the aggregate is more likely to be high in more severely ill patients.…”
Section: Discussionmentioning
confidence: 99%